2018
DOI: 10.1007/s11356-018-1602-5
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Multi-sensor temporal assessment of tropospheric nitrogen dioxide column densities over Pakistan

Abstract: The present address of Rabbia Murtaza is shown in this paper. (please tag the affiliation below, this is only for Rabbia Murtaza).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The higher value of CH in these cities may be due to industries, transport activities, energy sector, China, Pakistan Economic Corridor, and residential activates, etc. The urban areas showed high concentrations of chemicals as reported in China (Xiao et al 2014) and Pakistan (Murtaza et al 2018). The CH value range is recorded 1-1.2 kg/m 2 /s over Pakistan.…”
Section: Spatio-temporal Distribution Of Chlorinated Hydrocarbonsmentioning
confidence: 64%
See 1 more Smart Citation
“…The higher value of CH in these cities may be due to industries, transport activities, energy sector, China, Pakistan Economic Corridor, and residential activates, etc. The urban areas showed high concentrations of chemicals as reported in China (Xiao et al 2014) and Pakistan (Murtaza et al 2018). The CH value range is recorded 1-1.2 kg/m 2 /s over Pakistan.…”
Section: Spatio-temporal Distribution Of Chlorinated Hydrocarbonsmentioning
confidence: 64%
“…The results suggested that higher contribution of transport sectors might be due to the production and usage of CH in this sector as compared to other sectors. Another factor may be that most of the human activities (industrial area and the huge traffic) take place in the northern and eastern areas of Pakistan (Murtaza et al 2018). Karachi, Pakistan's largest city with a high percentage of industrial activities and fuel combustion, showed exceptionally high concentration in the south of the country.…”
Section: Sector-wise Distribution Of the Chlorinated Hydrocarbonmentioning
confidence: 99%